Output only structural identification in time domain Numerical and experimental studies. - Perry, M.J (Earthquake engineering & structural dynamics.)
By identifying changes in stiffness parameters, structural damage can be detected and monitored. Although considerable progress has been made in this research area, many challenges remain in achieving robust structural identification based on incomplete and noisy measurement signals. The identification task is made even more difficult if measurement of input force is to be eliminated. To this end, an output only structural identification strategy is proposed to identify unknown stiffness and damping parameters. A non classical approach based on genetic algorithms (GAs) is adopted. The proposed strategy makes use of the recently developed GA-based method of search space reduction, which has shown to be able to accurately and reliably identify structural parameters from measured input and output signals. By modifying the numerical integration scheme, input can be computed as the parameter identification task is in progress, thereby eliminating the need to measure forces. Numerical and experimental results demonstrate the power of the strategy in accurate and efficient identification of structural parameters and damage using only incomplete acceleration measurements.